Morphology and mechanical behaviour of pea-based starch-protein composites obtained by extrusion. (1st November 2019) - Jebalia, I.; Maigret, J.-E.; Réguerre, A.-L.; Novales, B.; Guessasma, S.; Lourdin, D.; Della Valle, G.; Kristiawan, M.
Graphical abstract: The composites mechanical properties are controlled by the starch-protein interface index which is governed by the specific mechanical energy (SME). Highlights: Pea composites were extruded in a large interval of specific mechanical energy SME. Various starch/protein composite morphologies can be obtained by modifying SME. An interface index is defined to describe composite morphology. The composites mechanical properties strongly depend on interface index. Abstract: Starch-legume protein composites were obtained by extrusion of pea flour and pea starch-protein blend at various specific mechanical energies (100–2000 kJ/kg) and a temperature low enough to avoid expansion. The morphology of these composites displayed protein aggregates dispersed in a starch matrix, revealed by microscopy. Image analysis was used to determine the median width of protein aggregates ( D50 ), their total perimeter and surface, from which a protein/starch interface index ( Ii ) was derived. The mechanical properties of composites were determined by a three-point bending test. The pea flour composites had a higher interface index Ii (1.8–3.1) with lower median particle width D50 (8–18 μm) and a more brittle behaviour than the blend composites that had a lower Ii (1–1.1) and higher D50 (22–31 μm). For both materials, rupture stress and strain were negatively correlated with Ii . This result suggested that there was a poor interfacial adhesion between the pea starch and proteins.